PEMBUATAN KOMPOS DARI LIMBAH KULIT PISANG KEPOK MENGGUNAKAN MIKROORGANISME EM-4 - Daryono Daryono (JURNAL AGRIMENT, 2017)
Banana peel is a lot of waste material, which is 1/3 of unpeeled bananas. In general, this banana fruit skin has not been exploited only thrown as a mere waste. This causes a loss, it would be nice if the banana peel can be utilized into something of economic value by processing it into organic compost fertilizer. This study only 1 treatment that is 5 kg banana kepok + 0,5 kg chicken manure + 10 cc EM-4 + 1 liter water. From the results of physical observation in this study compost process that has been mature black, this research crumbs time required in the composting process that is for 13 days by observing the color and smell of compost is odorless but smelly soil. At the time of composting shrinkage occurs, at the beginning of the manufacture of raw material compost 5 kg after mature compost shrinkage so that the final weight of compost 3 kg. While the chemical compost fertilizer already meets the Standards of Organic Fertilizer based on Regulation of the Minister of Agriculture no. 70 / Permentan / SR.140 / 10/2011 are N-Total 1.44%, P2O5 0.75%, K2O 9.45% and Fe 5288.44%.